2007
DOI: 10.4067/s0717-95022007000400028
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Complete Ossification of the Superior Transverse Scapular Ligament in Brazilians and its Clinical Implications

Abstract: SUMMARY:The aim of this study was to verify the prevalence of the ossified superior transverse scapular ligament (STSL) on dry bones of scapulae. 221 dry bones were analyzed, (111 rights and 110 lefts), proceeding from Rio de Janeiro and of Santa Catarina, Brazil. As exclusion criterion, were not analyzed bones of children or damaged. For the quantitative analysis of the data, the software Graphad Instat was used. Fisher exact test was used considering the p≤ 0,05 as significant. After analysis of the scapulae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 21 publications
5
25
3
1
Order By: Relevance
“…In present study, we found 12.5% incidence of completely ossified STSL which is close to findings of Jadhav et al [9] (10.57%). Silva et al [10] found the incidence of completely ossified STSL 30.76% in Brazilian population which is very high as compared to our study (12.5%). In some parts of world its incidence is very rare e.g.…”
Section: Introductioncontrasting
confidence: 68%
“…In present study, we found 12.5% incidence of completely ossified STSL which is close to findings of Jadhav et al [9] (10.57%). Silva et al [10] found the incidence of completely ossified STSL 30.76% in Brazilian population which is very high as compared to our study (12.5%). In some parts of world its incidence is very rare e.g.…”
Section: Introductioncontrasting
confidence: 68%
“…(3) However, a high incidence of ossified STSL does not proportionally correlate with the occurrence of SSN entrapment; (4,5) this could be due to the lack of focus on the influence that the body ridge shape (created by the ossified STSL) has on SSN entrapment. With this in mind, the present study was designed to analyse the variable morphological aspects of the ossified STSL, along with other ossified ligaments found in the scapula.…”
Section: Introductionmentioning
confidence: 97%
“…The incidence of the SN entrapment has been found higher in Brazilians, and the incidence of foraminae was found higher on right sides of male cadavers than left side (p < 0.05) [46]. Tubbs et al [50] concluded that higher rate of suprascapular foramina on right scapulae may be related to the right-hand dominance in general population.…”
Section: Discussionmentioning
confidence: 99%
“…There was no correlation between the notch type and the injury frequency although the differences of morphology were found in the notch [11,46]. The incidence of the SN entrapment has been found higher in Brazilians, and the incidence of foraminae was found higher on right sides of male cadavers than left side (p < 0.05) [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation